О ПРИБЛИЖЁННОМ РЕШЕНИИ КРАЕВОЙ ЗАДАЧИ ДЛЯ ИНТЕГРО-ДИФФЕРЕНЦИАЛЬНЫХ УРАВНЕНИЙ ФРЕДГОЛЬМА С ФУНКЦИОНАЛЬНЫМИ КРАЕВЫМИ УСЛОВИЯМИ - Нуржанов, Б.О.; Омаров, Т. (SCIENCE and SOCIETY, 2020)
The article deals with the substantiation of the numerical-analytic method of successive approximations for the study and approximate construction of solutions of a nonlinear system of Fredholm integro-differential equations with functional boundary conditions.